Pengaruh Etos Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Pos Indonesia (Persero) Pemalang - Saputro, Hersaptoto Adi; Subroto, Setyowati (Major Management, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
The effort to improve employee performance is by paying attention to work ethic and work discipline. Work ethic is an individual's way of expressing work which can be a driving force or drive for success, while discipline is one's awareness in complying with company regulations. The driving force and awareness of someone in complying with applicable regulations can create someone to be ready to work even work hard. This study examines the work ethic and work discipline that affect the performance employee of PT. Pos Indonesia (Persero) Pemalang. This study uses a quantitative approach with analytical tools used, namely Instrument Test (Validity and Reliability Test), Classic Assumption Test, Hypothesis Test (t Test and F Test), Multiple Regression Analysis and Determination Coefficient. The results showed (1) There was a positive and significant work ethic effect on performance employees. (2) There is a positive and significant effect of work discipline on performance employees. (3) There is an influence of work ethic and work discipline simultaneously on employee performance. The conclusion of this study shows that there is still a lack of work ethic and work discipliine that affects the performance of the employees of PT. Pos Indonesia (Persero) Pemalang.